As muitas faces de um autor: a construção do ethos retórico em contos machadianos - Alves, Andréia Carla Melegati Rodrigues (2016)
This thesis aims to present an analysis of the writer Machado de Assis’s ethe manifested in his short stories. The analysed corpus consists of three tales by that author. The objective is to ascertain the constitution of the rhetorical ethos of this short story writer / speaker and observe the argumentative strategies adopted by him aiming to gain his reader / audience’s trust. The theoretical framework used in this work includes the establishment of the ethos from the rhetorical studies grounded in the concepts of Aristotle (2005), Eggs (2005), Meyer (1993 and 2007), Perelman and Olbrechts-Tyteca (2005), Reboul (2004) and Tringali (1988). In this work, the study of rhetoric became important because it has within its scope of utilities, the collaboration to the process of interpreting texts. The analysis results showed that the storyteller / speaker Machado de Assis’s speech strength is guided by the confidence that he reveals in his speech by showing a speaker who has prudence, common sense, wisdom, honesty and sincerity. The analysis also showed that the discursive resources used by the speaker were fundamental for the storyteller to obtain the adhesion of his reader / audience. The choice of the three stories is explained by the popularity of them and because we consider them a sufficient sample to demonstrate how the speaker's image is built through the discourse. Regarding the methodological procedures used, it was executed, at first, a review of the theoretical literature mentioned; then proceeded to the corpus selection from Machado's work; finally, there was a qualitative and comparative analysis of the stories in question aiming to grasp the ethe showed. With this research, we hope to promote the expansion of the discussion on the rhetorical ethos, especially in its relation with the selected corpus: the tale. Keywords: rhetoric; ethos; tale; Machado de Assis.